Automated mineralogical characterization using optical microscopy: Review and recommendations. (November 2022) - De Castro, Benjamin; Benzaazoua, Mostafa; Chopard, Aurélie; Plante, Benoît
Highlights: A review of the evolution of automated optical microscope (OM) is provided. Automated OM constitutes an alternative to automated SEM-EDS. An improvement of optical cameras and classification procedures are recommended. Transparent gangue mineral detection/quantification is still the main limitation. Further application cases and comparative studies are recommended. Abstract: Automated mineralogical quantification has recently become an important aspect of geometallurgy. Automated scanning electron microscopes are most commonly used to perform automated mineralogical analysis. Automated optical microscopes can also perform automated mineralogical characterization, but its use is less common in mining industry. Nevertheless, the mining industry does not sufficiently perform mineralogical characterization during its operations. The main reason automated mineralogical characterization is underused is the significant capital cost and accessibility of this technique. In contrast, reflected optical microscopy is a more accessible and less restrictive device for automated quantitative mineralogical analysis. Automated optical microscopy does not require an advanced specialist operator, unlike automated scanning electron microscopy. The optical microscope, allowing the identification of opaque minerals (sulfides, oxides, and native elements/alloys etc.), could become advantageous for the characterization of mining products in a geometallurgical context. Especially for polymetallic/gold sulfide and iron oxide deposits where opaque minerals are valuable minerals and/or have a mineral processing and environmental interest. This paper reviews the evolution of the automated optical microscopy technique. This work illustrates: i) the development of automated optical microscopy, including improvements in image analysis and optical cameras; and ii) the presentation of comparative studies and applications for automated optical microscopy.